ANALISA UNJUK KERJA PROPELLER TYPE MAU PADA KAPAL PERINTIS 2000 GT DENGAN VARIASI SUDUT SKEW DAN SUDUT RAKE MENGGUNAKAN METODE CFD - Artha Akbar Jala; Muhadi Eko Muhammad; Gafur Abdul (Proceedings Conference on Marine Engineering and its Application, 2018)
The construction of new ships has many aspects to be considered, one of which is the aspect ofplanning in the field of propulsion system. The Aspect of the propulsion system includes propeller designplanning. Propeller is one of the important aspects that must be properly planned so that the ship can reachthe maximum speed. Speed on the ship is inseparable from the good propeller design in order to get maximumperformance from the ship propeller movement. The purpose of this research is to know the maximumpropeller performance from 24 models of MAU type propeller variation with variable of skew angle variationand rake angle. The calculation of Ship resistance is 105,705 KN. The results of this study shows a propellermodel with a skew angle variation of 45 ° and rake angle 0 ° has the highest thrust value of 119,447 KN. Thelowest torque value is generated on the propeller model with a skew angle variation of 10 ° and a rake angleof 15 ° at 20.534 KN m. And the highest efficiency value is generated on propeller model with skew anglevariation 10 ° and rake angle 0 ° equal to 56,33%. Propeller model that has the maximum performance is apropeller model with skew angle variation of 10 ° and rake angle 0 ° because it has the highest efficiencyvalue that is equal to 56,33%.